Endothelial downregulation of nuclear m6A reader YTHDC1 promotes pulmonary vascular remodeling in sugen hypoxia model of pulmonary hypertension - Hao Zheng; Di Wu; Xiangyu Chen; Wenjuan He; Jing Hua; Qiang Li; YingQun Ji (Heliyon, 2024)
Background: Pulmonary hypertension (PH) is characterized with vascular remodeling, which is intiated by vascular endothelial dysfunction. N6-methyladenosine (m6A) modification mediates gene expression in many ways including mediating RNA degradation, splicing, nuclear export et al. m6A modification have been found to be associated with the development of PH. However, the role of m6A regulators in pulmonary artery endothelial cells (PAECs) dysfunction of PH is still under research. Methods: The expression levels of m6A regulators in PAECs were analyzed with the single-cell sequencing Data(scRNA). Next, the target differentially expressed genes (DEGs) of m6A regulators in PAECs were functionally annotated. The analysis of cellular interactions included the examination of receptor—ligand pairs regulated by m6A regulators. Pseudo-time trajectory analyses and a ceRNA network involving lncRNAs, miRNAs, and mRNAs were conducted in PAECs. Furthermore, microarray data (GSE180169) for Sugen Hypoxia PH (SuHx PH) mouse models was screened for DEGs and m6A regulators in PAECs. Moreover, the expression of YTHDC1 in the lung samples of SuHx PH models was determined using immunofluorescence. In vitro, the mRNA expression of YTHDC1 in HPAECs under hypoxia conditions was detected. The effect of YTHDC1 recombinant protein on HPAEC proliferation was detected by Cell Counting Kit-8 (CCK8). Results: Dysregulation of m6A regulators was observed in mouse PAECs. The m6A reader of YTHDC1 was decreased in PAECs in scRNA data and RNAseq data of isolated PAECs of SuHx PH models. Downregulation of YTHDC1 was caused by hypoxia in PAECs in vitro and similar results was observed in PAECs of SuHx PH mouse models. Next, YTHDC1 recombinant protein was found to inhibit HPAECs proliferation. The DEGs targeted by YTHDC1 were enriched in angiogenesis, endothelial cell migration, fluid shear stress, and stem cell maintenance. Analysis indicates that interactions among endothelial cells, smooth muscle cells, fibroblasts, and immune cells, mediated by specific YTHDC1 target genes (e.g., PTPRC-MRC1, ITBG2-ICAM1, COL4A1-CD44), contribute to PH development. Also, the YTHDC1 expression were consistent with Thioredoxin interacting protein (TXNIP). What's more, the predicted transcription factors showed that NFKB1, Foxd3 may be involved in the regulation of YTHDC1. Lastly, our data suggest that YTHDC1 may be involved in regulating PAECs dysfunction through lncRNA/miRNA/mRNA network. Conclusion: For the first time, we analyzed changes in the expression and biological functions of m6A regulators in SuHx PH mouse models. We causatively linked YTHDC1 to PAECs dysfunction, providing novel insight into and opportunities to diagnose and treat PH.